Determination of Total Antioxidant and Phenolic Content from Malvaceae Family Leaves Infusion by Spectrophotometry - Yefrida Yefrida; Silvia Detri Susanti; Refilda Refilda (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2023)
The use of plants as a source of medicine has been increasing lately. The plants used generally have bioactivities such as anti-bacterial, antioxidant, and others. Plants that contain antioxidants are widely used because of their ability to capture free radicals so that they can protect the body from various diseases. One of the plants that is often used is plants from the Malvaceae family. In this study, the antioxidant and total phenolic contents of five types of plants were determined. These plants were extracted by infundation method and analyzed using MPM (Modified Phenanthroline Method) and Folin-Ciocalteu methods. The highest antioxidant and total phenolic contents were found in kapok randu and waru leaves.